The views of children and young people on the use of silk garments for the treatment of eczema: a nested qualitative study within the CLOTHing for the relief of Eczema Symptoms (CLOTHES) randomized controlled trial. (1st January 2018) - Wake, E.V.; Batchelor, J.; Lawton, S.; Thomas, K.S.; Harrison, E.F.; Cowdell, F.C.; ,; Williams, Hywel; Llewellyn, Jo; Dean, Taraneh; Grundy, Jane; Pollock, Ian; et al.
Summary: Background: Many children suffer with skin diseases but to date most dermatological research has been done 'on' rather than 'with' children; in this study we actively sought the experiences of children and young people. Atopic eczema (AE) is a chronic, itchy, inflammatory skin condition that affects around 20% of children and can impact on the health and wellbeing of children and their families. The role of specialist clothing in the management of AE is poorly understood. Objectives: The aim of this study, which was nested in a randomized controlled trial, was to qualitatively examine child participants' experiences of using silk garments for the treatment of AE. Methods: Eighteen children aged 5–15 years, who took part in the CLOTHing for the relief of Eczema Symptoms (CLOTHES) trial, participated in age‐appropriate individual interviews or focus groups. Results: Thematic analysis generated four themes directly related to the silk garments: (i) expectations of the garments; (ii) wearing the garments; (iii) asking if the garments helped; and (iv) thoughts about the garments. The conclusions from this nested qualitative study are that there was some limited improvement in eczema for some children but that the hoped‐for 'miracle cure' did not transpire. A mixed picture of knowledge, beliefs and experiences of using the silk garments emerged. Conclusions: Engaging children in the evaluation of the garments provided first‐hand nuanced insights that enhanced understanding of the CLOTHES study as a whole. This nested study demonstrates that children can and indeed want to be engaged in dermatological research in meaningful ways that add to our understanding of treatment options.